Analisis Beban Kerja Mental Pada Area Fabrikasi Tanki Delta 101 Menggunakan Metode NASA-TLX Di PT.XYZ - Reihan Bintang Yuliandana; Ayudyah Eka Apsari (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2025)
This study was carried out at PT XYZ, a business involved in the oil and gas sector, located in Indramayu, West Java. The objective of this study is to identify and analyze the mental workload existing at PT XYZ by examining the Weight Workload (WWL) values. The research method used is NASA-TLX. The population for this study consists of 10 workers in the Delta 101 Tank Fabrication section at PT XYZ, totaling 10 individuals. Based on the study, the results of the mental workload calculations for the Delta 101 Tank Fabrication mechanics indicated that out of the 10 respondents, 2 mechanics were categorized as having a High workload. These mechanics are Mechanic 3, aged 53, Mechanic 5, aged 50, and Mechanic 8, aged 52, with a score of 90.7, which falls into the Very High category. The lowest score was obtained by Mechanic 7, aged 29, with a score of 77.3, categorized as High. The researcher provides suggestions for improvements that are expected to help the company address existing issues. The proposed improvements include recommending the addition of workforce; having additional personnel could reduce double job responsibilities, ensuring that installation and welding tasks are performed by different mechanics, thus optimizing the Tank Fabrication process.